Communication Barriers of Community Counselors (PK) to Child Clients: A Study at the Class I Correctional Center Office in Bengkulu - Lestari, Yani; Octaviani, Vethy; Yanto, Yanto (Universitas Dehasen Bengkulu, 2025)
This study aims to explore the communication barriers experienced by Community Counselors (PK) in their interactions with child clients at the Class I Correctional Center Office in Bengkulu. Employing a qualitative descriptive approach, data were collected through interviews, observation, and documentation involving six informants (three key informants and three supporting informants). The study adopts Fajar’s (2009) theory, which categorizes communication barriers into four types: sender-related, encoding and symbols, media, and receiver-related obstacles. The findings reveal that sender-related barriers are still prevalent, particularly influenced by the psychological and emotional conditions of the child clients. Despite efforts to simplify messages, one counselor reported difficulties due to the complex backgrounds of some children. However, encoding and symbolic barriers were not found, as all counselors used simple and clear language, supported by concrete examples to ensure comprehension. Media-related barriers were also minimal since all communication was conducted face-to-face without reliance on electronic media. From the client’s perspective, most child clients demonstrated an adequate understanding of the messages delivered, citing the clarity of language and a comfortable counseling atmosphere as key factors. Nevertheless, some clients expressed confusion due to the use of unfamiliar terms or fast-paced explanations. This research emphasizes the importance of adaptive communication strategies in child rehabilitation settings and suggests training interventions to enhance the interpersonal communication skills of PK staff when dealing with diverse child client profiles.